Adventization of Dendroflora of the Orel River Valley (Ukraine) - Ivanko, Iryna; Gorban, Vadym (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The purpose of our study is to establish the features of the adventization of the flora of trees and shrubs in the valley of the Orel River. As a result of geobotanical studies it was established that the tree-shrub vegetation in the valley of the river. The eagle is represented by natural forests, artificial plantations and semi-natural plantations, among which natural forests of oak (Quercus robur) and artificial plantations of pine-tree (Pinus sylvestris) and black locust (Robinia pseudoacacia) are predominant. It was revealed that within the taxonomic composition of the dendroflora of the valley of the Orel River (95 woody and shrubby species) the adventive fraction consists of 33 species (35%), which belong to 18 families. Within the area studied, 17 species were naturalized into the adventitious fractions of dendroflora. By origin in the adventive fraction of dendroflora the species with Asian (10 species – 30%) and North American (10 species – 30%) primary areas predominate. Other microelements are represented by single species and 4 species – with an unidentified primary area (anecophytes). Six woody-shrubby species show invasive activity in phytocenoses of the valley of the Orel River. They are invasive neophytes: Robinia pseudoacacia L., Acer negundo L., Ulmus pumila L., Elaeagnus angustifolia L., Amorpha fruticosa L., Partenocissus quinquefolia (L.) Planch. Now they are naturalized and actively infect various types of biotopes: the coastal zones of the Orel River and its tributaries, beams, natural and artificial forests, and more recently – lands that are withdrawn from agricultural use. The intensive adventitization of the dendroflora of the valley of the Orel river was discovered. It shows the anthropogenic transformation of this territory. The introduced neophytes have recently been actively naturalized and are the part of the natural phytocoenosis, changing their structure, which poses a threat to natural biodiversity. This requires further monitoring studies of the state of the flora of this territory, as well as observations of naturalization processes and the build-up of the invasive ability of adventive species.